[Development of the short version of the informal caregiver burden assessment questionnaire] - Martins, T. (2015)
OBJETIVE to create a reduced version of the QASCI, which is structurally equivalent to the long one and meets the criteria of reliability and validity. METHOD Through secondary data from previous studies, the participants were divided into two samples, one for the development of reduced version and the second for study of the factorial validity. Participants responded to QASCI, the SF 36, the ADHS and demographic questions. RESULTS A reduced version of 14 items showed adequate psychometric properties of validity and internal consistency, adapted to a heptadimensional structure that assesses positive and negative aspects of care. CONCLUSION Confirmatory factor analysis revealed a good fit with the advocated theoretical model.